Fracture modelling of adhesively-bonded joints by an inverse method (Fracture and Structural Integrity, 2019)
Nowadays, any structure must have strength, robustness and lightness, which has increased the industrial interest and research efforts in adhesive joining, mainly in the improvement of strength and fracture properties of adhesives. Thus, in recent years, the use of adhesive joints in industrial applications has gradually grown, replacing some traditional bonding methods, since they have advantages such as reduced stress concentrations, reduced weight and cost, and ease of processing/manufacturing. In this work, the cohesive laws of three adhesives, Araldite® AV138, Araldite® 2015 and Sikaforce® 7752, were obtained by the application of an inverse adjustment method between the numerical and experimental load-displacement curves (P-d) of Double-Cantilever Beam (DCB) tests for tensile characterization and End-Notched Flexure (ENF) tests for shear characterization. Next, these laws were validated with experimental data of single-lap joints (SLJ) and double-lap joints (DLJ), using Abaqus®. For the Araldite® AV138 and Araldite® 2015, in tension and shear, the triangular law accurately predicted the behaviour of the SLJ and DLJ. For the Sikaforce® 7752, the triangular law did not suitably fit the experimental results. It was considered that, due to its ductility, the Sikaforce® 7752 is best modelled with a trapezoidal law.
Keywords: Adhesive joint; Structural adhesive; Cohesive zone models; Inverse method; Parameter identification